2021
DOI: 10.1007/s00394-021-02733-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed food consumption in adults across Europe

Abstract: Purpose The purpose of this study is to describe ultra-processed food and drinks (UPFDs) consumption, and associations with intake of total sugar and dietary fibre, and high BMI in adults across Europe. Methods Using food consumption data collected by food records or 24-h dietary recalls available from the European Food Safety Authority (EFSA) Comprehensive European Food Consumption Database, the foods consumed were classified by the level of processing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 39 publications
2
39
1
2
Order By: Relevance
“…Comparing our results with other studies is difficult because the way foods are grouped differs from one study to another. However, a study conducted in 22 European countries reported that the two main UPFs consumed among adults were fine bakery wares and sausages [ 43 ]. In our study, chocolate, industrial cakes, and cookies are typical UPFs of the group confectionary, cakes & biscuits.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing our results with other studies is difficult because the way foods are grouped differs from one study to another. However, a study conducted in 22 European countries reported that the two main UPFs consumed among adults were fine bakery wares and sausages [ 43 ]. In our study, chocolate, industrial cakes, and cookies are typical UPFs of the group confectionary, cakes & biscuits.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of such diseases does indeed increase with UPF intake within populations but, importantly, not across populations. In countries such as the United Kingdom or Ireland, where their level of consumption exceeds 50% of total food, the incidence of UPF-associated NCDs should be much higher than in countries like Italy, where instead it only slightly exceeds 10% (82) , but this is not the case.…”
Section: Nova Classification and Poor Prognosis In Epidemiological St...mentioning
confidence: 95%
“…The consumption of ultra-processed foods with increasing wealth might be a confounding factor contributing to the increased incidence of breast cancer worldwide [ 51 ]. However, it is important to note that while Europe has seen an increase in breast cancer incidence overall, processed food consumption in women has fallen in Austria, Belgium, Denmark, the Netherlands, Sweden [ 52 ]; countries where incidence increased or remained elevated. Thus, while increased processed food consumption in non-European countries might have contributed to increased breast cancer incidence, it cannot account for the increased breast cancer incidence in Europe.…”
Section: Discussionmentioning
confidence: 99%